PENGARUH PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP PEMBENTUKAN MORAL REMAJA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Andiny Nur Hekmah; Feni Fathniani; Nurlaela; Rahmawati Rossy; Salsabila Hamilaturrohmah; Moch. Mahdiyan Nasikhin (PT. Hasba Edukasi Mandiri, 2026)
The rapid development of information technology, particularly social media, poses significant moral challenges for adolescents (Generation Z). This study examines how the intensity and quality of information technology use affects adolescent morality, the extent to which local values such as Pancasila and Islamic religious teachings shape their digital ethics, and what strategies are most effective in restoring social responsibility in the digital era. Employing a qualitative literature review method, this paper analyzes relevant studies on digital literacy, adolescent moral development, and Islamic education values. The findings indicate that information technology has a dual impact: it offers opportunities for self-expression, collaborative learning, and access to information, while simultaneously posing risks such as cyberbullying, hoax dissemination, hate speech, and moral degradation. Religious values and community-based approaches, particularly through Islamic education, prove effective in building adolescent digital ethics. The study concludes that an integrated approach—combining digital literacy education, character education rooted in Islamic values, parental supervision, and policy support—is essential to guide adolescents toward responsible and ethical technology use.